Benzimidazole derivatives as potential dual inhibitors for poly (adp-ribose) polymerase-1 and dihydroorotate dehydrogenase / Iskandar Abdullah - Iskandar, Abdullah (2015)

(untitled)
Poly (ADP-ribose) polymerases (PARPs) play diverse roles in various cellular processes that involve DNA repair and programmed cell death. Amongst these polymerases is PARP-1, which is the key DNA damage-sensing enzyme that acts as an initiator for the DNA repair mechanism. Dihydroorotate dehydrogenase (DHODH) is an enzyme in the pyrimidine biosynthetic pathway and has been an important target for anti-hyperproliferative and anti-inflammatory drug design. Since these enzymes share a common objective in the DNA replication and repair mechanisms, it may be beneficial to target both PARP-1 and DHODH in our attempt to design new anti-cancer agents. Benzimidazole derivatives have shown a wide variety of pharmacological activities including PARP-1 and DHODH inhibition. Thus, molecular modeling, synthesis and bioactivity evaluation of a series of benzimidazole derivatives using PARP-1 colorimetric assay and DHODH enzymatic assay were carried out in the search of dual inhibitors for both PARP-1 and DHODH enzymes. Independently, compounds 9h, 10b, 10c, 10f, 10h and 11e displayed good activities in PARP-1 enzyme while compounds 7b, 7e, 7f and 7g exhibited good activities in DHODH enzyme. Nevertheless, dual inhibition activities for both of PARP-1 and DHODH enzymes were demonstrated by compounds 7e, 9h, 10h and 11e albeit low activity was observed.